The effect of smartphone use on trends in European adolescents' excessive Internet use. Issue 1 (2nd January 2016) - Škařupová, Kateřina; Ólafsson, Kjartan; Blinka, Lukas
ABSTRACT: Despite growing public health concerns data on excessive Internet use (EIU) allowing for comparison between countries and over time are scarce. Our study is the first attempt to evaluate the changes and the impact of mobile access on EIU in Europe. It is based on data from 2 surveys of adolescents implemented in 2010 and 2013 in 7 European countries that used identical methodology; a total of 7663 adolescents were recruited by random stratified sampling. The levels of EIU were compared and a regression model was used to assess the impact of smart devices, the number of activities performed online, and the specific online applications. A small but significant increase of EIU levels was observed in Belgium, Denmark, Romania, the UK, and overall. Although smartphone use is a positive predictor of EIU, it is moderated by the increasing number of activities performed online. The increase in levels of EIU is also associated with the daily use of online games and social networking sites.